Attitudes Toward the Physically Disabled Persons: Do Education and Personal Contact Make a Difference? - Gosse, Verena F.; Sheppard, Glenn (Canadian Journal of Counselling and Psychotherapy, 2012)
This study compared the attitudes toward physically disabled persons held by individuals at three educational levels who had personal contact versus no such contact with the disabled. Data analyses revealed a significant main effect for education. The higher their educational level the more positive were the students' attitudes with the exception of no significant differences between grade eleven and university students. The main effect for contact indicated that, in general, those who had contact with physically disabled persons were more favorable in their attitudes than those who had had no contact. However, an examination of subgroup means showed no differences between grade XI contact and no-contact groups. The interaction effect between education and contact did not appear to be linear. Various explanations for these results are mentioned with the implication such findings may have for current efforts at educational mainstreaming.